Mount S. Benedict, Trinidad, B.W.I. : Garden With Fountain - (:unkn) unknown (My University, 2010)
Photo of Mount St. Benedict in Trinidad and Tobago. No. 8. Hand-written letter.
Colour: White, Green, Grey and Cream Hues; Style: Landscape; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Catholic Church--Trinidad and Tobago; Monasteries--Trinidad and Tobago; Christianity--Trinidad and Tobago; Catholics--Trinidad and Tobago; Catholic church buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Fountains--Trinidad and Tobago; Gardens--Trinidad and Tobago; Church gardens--Trinidad and Tobago; Mt. St. Benedict